2019
DOI: 10.1021/acsaem.9b00407
|View full text |Cite
|
Sign up to set email alerts
|

Photocharging of Europium(III) Tellurium Oxide as a Photoelectrocatalyst

Abstract: This work reveals that Eu2TeO6, as a photoelectrocatalyst, exhibits a sustained photocharging effect that results in an enhanced and “sustained” dark current (subsequent to the termination of illumination), which is greater than the current obtained through applied electrical potential alone. Samples of europium tellurium oxide, prepared through the employment of a Pechini sol–gel route and calcined at 400 and 900 °C, were characterized for selective physicochemical properties and comparatively evaluated as an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 43 publications
2
9
0
Order By: Relevance
“…19 There are a few instances in which Ni-based oxides and oxyhydroxides have been used as cocatalysts to enhance the efficiency of PEC activity, namely, Ni/TiO 2 nanotubes, 20 α-Fe 2 O 3 /NiCeO x , 19 NiOOH-coated codoped (Sn, Zr) α-Fe 2 O 3 , 21 etc. Having earlier reported on the remarkable ability of europium(III) tellurium oxide to photocharge and utilize the stored charge to split water (in the dark), 22 we now report on nickel(II) tellurium oxide exhibiting the same phenomenon. As nickel tellurium oxides display outstanding optical, magnetic, and ferroelectric properties, 23,24 it was synthesized via a Pechini sol−gel route and successively sintered at different temperatures.…”
Section: ■ Introductionsupporting
confidence: 55%
See 3 more Smart Citations
“…19 There are a few instances in which Ni-based oxides and oxyhydroxides have been used as cocatalysts to enhance the efficiency of PEC activity, namely, Ni/TiO 2 nanotubes, 20 α-Fe 2 O 3 /NiCeO x , 19 NiOOH-coated codoped (Sn, Zr) α-Fe 2 O 3 , 21 etc. Having earlier reported on the remarkable ability of europium(III) tellurium oxide to photocharge and utilize the stored charge to split water (in the dark), 22 we now report on nickel(II) tellurium oxide exhibiting the same phenomenon. As nickel tellurium oxides display outstanding optical, magnetic, and ferroelectric properties, 23,24 it was synthesized via a Pechini sol−gel route and successively sintered at different temperatures.…”
Section: ■ Introductionsupporting
confidence: 55%
“…This is consistent with what is published in the literature for similar systems. 22,31 The overall fit (thick line) superimposes very well onto the raw experimental data (filled black circles) for all three samples. Component O1 is located on the lower BE side of the spectrum and takes up the majority of the spectral weight of this core level.…”
Section: Acs Applied Energy Materialsmentioning
confidence: 73%
See 2 more Smart Citations
“…This framework is prone to collapse during drying, which reduces the uniformity of the gel. A number of studies have shown that the calcination temperature has a great influence on the nature of metal oxides. High calcination temperatures favor the crystal growth but too high ones accelerate sintering, resulting in a sharp decrease in the specific surface area. For example, as the calcination temperature increases from 800 to 900 °C, the specific surface area of Ni 6 Mo 6 C decreases from 96 to 5 m 2 /g …”
Section: Introductionmentioning
confidence: 99%